Primary Teachers’ Beliefs about the Teaching of Grammar in Years 2 and 6 - Ingle, Janet (2017)
Despite the lack of conclusive evidence that the teaching of grammar improves primary school children’s writing, the National Curriculum (DfE 2013) places strong emphasis on the teaching of grammar with statutory tests of grammar at the end of Key Stage 1 and Key Stage 2. Within this context, this dissertation explores the beliefs of seven teachers about grammar, the teaching of grammar and the grammar tests at the end of Key Stages 1 and 2. It finds that after initial anxiety about teaching grammar, teachers have gained in subject knowledge and confidence. Teachers show awareness of both prescriptive and rhetorical models of grammar (Lefstein 2009) although they do not use those terms and use a variety of activities to promote engagement by children. Key Stage 2 teachers believe that there is too much grammar content in the National Curriculum, some of which is inappropriate to eleven-year olds, resulting in less time for more creative aspects of English. Teachers in this study see improvements in the written work of some children but not all. The majority of participants enjoy teaching grammar and believe that children enjoy learning it. They are considerably less enthusiastic about the Grammar, Punctuation and Spelling tests, which many believe are too difficult and of little value in assessment. Some teachers express strong negative feelings about the tests which they consider stressful for children. This dissertation concludes that there is a need for further study of this subject on a larger scale.